2017
DOI: 10.4040/jkan.2017.47.6.756
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Smart Program for Patients Who Underwent Percutaneous Coronary Intervention (SP-PCI) on Disease-Related Knowledge, Health Behavior, and Quality of Life: A Non-Randomized Controlled Trial

Abstract: This is an Open Access article distributed under the terms of the Creative Commons Attribution NoDerivs License. (http://creativecommons.org/licenses/by-nd/4.0)If the original work is properly cited and retained without any modification or reproduction, it can be used and re-distributed in any format and medium. Purpose: To identify the effects of a smart program for the patients who underwent percutaneous coronary intervention (SP-PCI) on coronary disease-related knowledge, health behaviors, and quality of li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Many hospitals currently use Plus Friend for hospital marketing by communicating hospital news and various consultation services. Lee reported that a smart program using KakaoTalk for patients improved their knowledge of disease and the performance of health behaviors [12]; however, the researcher must respond to patients' reactions individually, requiring personnel to operate the program. We used the Watson conversation launch tool to enable the automatic chat function, which not only reduced operating costs and efforts but also allowed real-time reactions to the participants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many hospitals currently use Plus Friend for hospital marketing by communicating hospital news and various consultation services. Lee reported that a smart program using KakaoTalk for patients improved their knowledge of disease and the performance of health behaviors [12]; however, the researcher must respond to patients' reactions individually, requiring personnel to operate the program. We used the Watson conversation launch tool to enable the automatic chat function, which not only reduced operating costs and efforts but also allowed real-time reactions to the participants.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, they can effectively provide sustained health behavior interventions. A Korean study has found that a smart program using KakaoTalk for patients who underwent percutaneous coronary intervention was easy to use, cost-effective, and improved knowledge of the disease and the performance of health behaviors [12]. KakaoTalk has the advantage of allowing users to check whether messages are received or not, and it allows more personalized intervention than a telephone consultation [12].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the present study found that the proportion of nonadherent subjects was low, and that subjects self-monitoring their physiological parameters and interpreting their significance led to improvements, while the self-management behavior and parameters were within the normal ranges. When implementing an intervention, variations in individual characteristics and proficiency of device use must be considered to ensure that the mobile app is utilized effectively [17]. Therefore, it is necessary to educate subjects about device use and prepare a support system when planning an intervention.…”
Section: Discussionmentioning
confidence: 99%
“…While some apps have been developed and are being utilized as essential tools for maintaining health, most of the related studies have involved middle-aged populations [15][16][17], and these apps are not ideal for application to elderly patients in clinical settings. However, it has been shown that the intention to accept smartphone-based health management approaches among elderly and chronic-disease patients is high, and an important reason for using the Internet is to obtain health-related information [18].…”
mentioning
confidence: 99%